Overview of the Human Papillomavirus (HPV) combat in Brazil and Worldwide: A literature review focused on educational strategies (Research, Society and Development, 2021)
Human Papillomavirus (HPV) is a virus transmitted sexually through sexual contact with or without penetration. Through the Brazilian National Immunization Program (PNI), the quadrivalent vaccine that prevents infection by serotypes 6, 11, 16 and 18 was inserted in 2014. Despite the incorporation of the vaccine, the number of hospitalizations for cervical carcinoma in situ is the third most recurrent among women in the fertile age group. The objective of the present study was to evaluate educational strategies that contribute to the expansion of vaccine adherence to HPV. The methodology was an integrative literature review using the LILACS, SciELO and MEDLINE databases. The descriptors used were: "HPV", "VACCINATION" and "EDUCATION". Articles published in the last 7 (seven) years were selected. It was observed that the knowledge of parents and adolescents in relation to HPV vaccination is not sufficient, and educational strategies are needed to increase adherence to immunization. The lack of educational methods that reach different audiences contributes to the failure to reach adequate levels of vaccination coverage. In addition, this scenario is not only seen in Brazil, but also in other countries that also publish studies that assess the need for educational measures aimed at increasing the fight against HPV, showing that global efforts can be of paramount importance in this context.